Analisis Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Hazard Identification Risk Assessment Determining Control (HIRADC) di Pt Bumi Sarana Beton - Perdana, Ilham; Anis Saleh; Taufik Nur (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The background of this research focuses on the importance of OHS in the manufacture field, especially considering the high number of work accidents reported by BPJS Ketenagakerjaan. This research aims to identify and assess the risk of hazards at PT Bumi Sarana Beton using Hazard Identification Risk Assessment Determining Control (HIRADC) and provide solutions to reduce work accidents. The HIRADC method is used to identify hazards, assess risks, and determine appropriate controls in accordance with the AS/NZS 4360: 2004 standard. The results showed that the production work area has several high risks such as pinching, respiratory distress, and slipping. Effective risk control implementation is expected to improve work safety and productivity. These findings have important implications for the management of PT Bumi Sarana Beton to improve OHS policies and provide adequate training and protective equipment for workers. In addition, this research is also expected to be a reference for other industries in implementing OHS optimally to reduce the risk of work accidents and improve workers' welfare